Kriptografik tizimlar algoritmlarining tahlili. (Conference Zone, 2022)
Government policy in the field of information technology aims to create a national information system, taking into account the modern world principles of developing and improving information resources, information technology and information systems. The problem of ensuring the state's information security is the main and integral part of ensuring national security, and information protection is becoming the primary issues of the state and the level of government policy. It is achieved by conducting a single policy of measures to protect the information of computer networks and a system of measures of legal, organizational, administrative, and administrative nature. That is why "cryptographic protection of information " is introduced in each country.